(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Language and human as the user of language will be never be one without other, because language and people are complementing each other. The phenomenon of using English abbreviation, acronym, and initialism will be found easily in the people‘s daily activities in especially some activities by network in facebook. This phenomenon occurs because people mostly use informal language in social media, because they just follow the other do something trendy on people in facebook, people use initialism mostly. Another form that people use are acronym and abbreviation